Efektivitas Pembelajaran Diferensiasi Berbasis Project Based Learning (PjBL) terhadap Pemahaman Konsep Matematika Siswa SMK - Nurdyanti Suaedy; Fatimah (Lembaga Yasin AlSys, 2026)
Although differentiated instruction and Project-Based Learning (PjBL) have been widely implemented in mathematics education, studies on the effectiveness of integrating these two approaches in improving vocational high school students’ understanding of mathematical concepts remain limited. This study aimed to describe the effectiveness of PjBL-based differentiated instruction in improving students’ understanding of mathematical concepts at SMK Kehutanan Negeri Makassar. The study employed a quantitative approach with a pre-experimental design. The research sample consisted of 34 students from Class XI-A selected using cluster sampling. Data were collected through a learning implementation observation sheet, a student activity observation sheet, a student response questionnaire, and learning outcome tests in the form of a pretest and posttest. The data were analyzed using descriptive and inferential statistical techniques. The results showed that PjBL-based differentiated instruction met the effectiveness criteria, as indicated by learning implementation categorized as mostly implemented, active student participation, and student responses categorized as good, with a mean score of 2.04. The students’ mean score for understanding mathematical concepts increased from 62.26 on the pretest to 81.44 on the posttest, with the level of improvement predominantly categorized as moderate for 30 students and low for four students. These findings confirm that PjBL-based differentiated instruction is effective in improving vocational high school students’ understanding of mathematical concepts. This study contributes theoretically to the development of the integration of differentiated instruction and PjBL and provides practical implications for teachers in designing mathematics instruction centered on students’ diverse learning needs.